Diagnosis dan Tatalaksana Prostatitis - Ali Ramzi; Fatimah Firza; Hadijatul Qubro (Faculty of Medicine, Universitas Mataram, 2026)
Prostatitis is a common urological condition in men of all ages, ranging from acute and chronic bacterial prostatitis to chronic pelvic pain syndrome (CP/CPPS) and asymptomatic inflammatory prostatitis. The condition is characterized by pelvic pain, lower urinary tract symptoms, and, in some cases, sexual dysfunction, significantly affecting quality of life. Major risk factors include bacterial infection, chronic inflammation, and functional obstruction. Pathophysiology involves bacterial invasion, immune response, and neuromuscular dysfunction in CP/CPPS. Management depends on the type of prostatitis and includes antibiotics for bacterial prostatitis, alpha-blockers, anti-inflammatory agents, and multimodal approaches such as the UPOINT system for CP/CPPS, while asymptomatic cases require monitoring. Early diagnosis and tailored therapy are essential to reduce complications and improve patient outcomes